2011
DOI: 10.2215/cjn.01000211
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Hepcidin-25 and Risk of Acute Kidney Injury Following Cardiopulmonary Bypass

Abstract: SummaryBackground and objectives Acute kidney injury (AKI) complicating cardiopulmonary bypass (CPB) results in increased morbidity and mortality. Urinary hepcidin-25 has been shown to be elevated in patients who do not develop AKI after CPB using semiquantitative mass spectrometry (SELDI TOF-MS). The goals of this study were to quantitatively validate these findings with ELISA and evaluate the diagnostic performance of hepcidin-25 for AKI.Design, setting, participants, & measurements A nested, case-control an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 33 publications
8
57
0
Order By: Relevance
“…Furthermore, iron chelation with deferoxamine has been reported to provide protection and significantly improve the severity and outcomes of AKI (2,3,5,(15)(16)(17)(18)(19)(20)(21)33). Additionally, other endogenous proteins involved in iron regulation and chelation, such as hepcidin and NGAL, have been shown to protect against AKI (21,(34)(35)(36)(37). Our current findings corroborate the injurious role of iron in AKI and delineate the renal proximal tubule as the major site of iron-induced injury.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, iron chelation with deferoxamine has been reported to provide protection and significantly improve the severity and outcomes of AKI (2,3,5,(15)(16)(17)(18)(19)(20)(21)33). Additionally, other endogenous proteins involved in iron regulation and chelation, such as hepcidin and NGAL, have been shown to protect against AKI (21,(34)(35)(36)(37). Our current findings corroborate the injurious role of iron in AKI and delineate the renal proximal tubule as the major site of iron-induced injury.…”
Section: Discussionsupporting
confidence: 79%
“…31 Although human studies have indicated a positive correlation between increased urinary hepcidin levels and protection against AKI, its direct role has not been examined in any models of AKI. 32 Here, we present evidence that renal IRI induces dynamic changes in renal and extrarenal iron homeostasis. Hepcidin-deficient mice sustain more severe renal injury after IRI and synthetic hepcidin mitigates renal IRI.…”
mentioning
confidence: 75%
“…16 Nevertheless, urinary hepcidin measurements may have utility in specific conditions, such as noninvasive measurement in children, screening in low-resource settings, or prediction of acute kidney injury. 17 …”
Section: Hepcidin Structure and Kineticsmentioning
confidence: 99%